1936
DOI: 10.1021/ja01295a002
|View full text |Cite
|
Sign up to set email alerts
|

The Hydrogen Bond between Oxygen Atoms in Some Organic Compounds

Abstract: The only serious discrepancy between these Weights are corrected to vacuum. values and the International values is with cad-Thb Atomic Weight of Protactinium Ratio KiPaF:, g. ß , g.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

1939
1939
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(36 citation statements)
references
References 0 publications
1
35
0
Order By: Relevance
“…Thus, the hydrogen bond provides special promise for the study of such interactions. It has been known for a long time (Hubert et al 1936;Ellis and Bath 1940) that the observed stretching frequency of a covalently bound hydrogen atom is perturbed in a specific way when that atom gets involved in hydrogen bonding to an acceptor group. These infrared shifts have given us a broad knowledge of the structural requirements for hydrogen bonding, both at inter-and intramolecular levels Marchessault 1959 a, 1959b;Marchessault and Liang 1960).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the hydrogen bond provides special promise for the study of such interactions. It has been known for a long time (Hubert et al 1936;Ellis and Bath 1940) that the observed stretching frequency of a covalently bound hydrogen atom is perturbed in a specific way when that atom gets involved in hydrogen bonding to an acceptor group. These infrared shifts have given us a broad knowledge of the structural requirements for hydrogen bonding, both at inter-and intramolecular levels Marchessault 1959 a, 1959b;Marchessault and Liang 1960).…”
Section: Resultsmentioning
confidence: 99%
“…According to Pimentel and McClellan, the peak corresponding to the X-H stretch in the IR spectrum offers the "most sensitive, the most characteristic and one of the most informative manifestation of H bond". Hilbert et al had concluded in 1936 that following the hydrogen bond formation, the X-H stretching peak disappears from the spectrum [119]. Shortly thereafter, Badger and Bauer [120] showed that the X-H stretching peak does not disappear but gets red-shifted to a lower wave number, the shift correlating with the strength of the hydrogen bond in X-HؒؒؒY [11,120].…”
Section: Spectroscopic Evidencementioning
confidence: 99%
“…Iogansen has shown the strong correlation between hydrogen-bonding energy and the increase in intensity of XH stretching band [38]. Conversely, the intensity of the first X-H stretching overtone is weaker than that observed in the monomer upon hydrogen bonding [119,122,123] and the red-shift is approximately double that observed in the fundamental [3,124]. For several years, the "disappearance" of the first overtone was used as a criterion for strong hydrogen bonding [3].…”
Section: Spectroscopic Evidencementioning
confidence: 99%
“…Indeed, eighty years ago failure to observe a OH stretching overtone was correlated with the presence of an H-bond. 15 Di Paolo et al 14 explained this in terms of a balance between mechanical and electrical anhrmonicity. Suhm and co-workers' studies of a range of alcohol dimers 10,11 report fundamental-to-overtone intensity ratios in the range of 300 to 1000 for the H-bonded OH stretches, compared to about 10 for the monomeric OH.…”
Section: Introductionmentioning
confidence: 99%